2013
DOI: 10.1016/j.actbio.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembling peptide matrix used to control stiffness and binding site density supports the formation of microvascular networks in three dimensions

Abstract: A three-dimensional (3-D) cell culture system that allows control of both substrate stiffness and integrin binding density was created and characterized. This system consisted of two self-assembling peptide (SAP) sequences that were mixed in different ratios to achieve the desired gel stiffness and adhesiveness. The specific peptides used were KFE ((acetyl)-FKFEFKFE-CONH2), which has previously been reported not to support cell adhesion or MVN formation, and KFE-RGD ((acetyl)-GRGDSP-GG-FKFEFKFE-CONH2), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 67 publications
2
41
0
Order By: Relevance
“…In contrast, the absence of RGD induced round morphology at all rigidities. Overall, these findings reveal the potential to control both the binding site density and the substrate stiffness within 3D cell-populated hydrogels and demonstrate the crucial influence of both adhesion and stiffness on cell type-specific cellular behaviors [433]. …”
Section: Human Tissue Ecm-based Biomaterialsmentioning
confidence: 99%
“…In contrast, the absence of RGD induced round morphology at all rigidities. Overall, these findings reveal the potential to control both the binding site density and the substrate stiffness within 3D cell-populated hydrogels and demonstrate the crucial influence of both adhesion and stiffness on cell type-specific cellular behaviors [433]. …”
Section: Human Tissue Ecm-based Biomaterialsmentioning
confidence: 99%
“…Several studies have shown peptide hydrogel systems with tuneable stiffness, where tuning is mainly achieved by varying peptide concentrations in the hydrogels . Some attempts to change hydrogel stiffness by varying amino acid composition in peptide amphiphilic systems has been explored, highlighting the key role of hydrophobic interactions in gel stiffness .…”
Section: Introductionmentioning
confidence: 99%
“…Even though several studies were conducted on the effect of SAP on MSCs in in vitro studies, [49][50][51] the fate of MSCs injected into the joint cavity will be different according to the microenvironments, as stem cells have high susceptibility to diverse microenvironments, including mechanical strain, shear stress, and cell-cell interaction, and will show altered differentiation and paracrine effects. 52,53 Wang 54 suggested the migration of injected MSCs from the injection site to the cartilage defect through the evidence of Prussian blue-positive and bromodeoxyuridine-labeled cells entering into the defect, which can be applied to our study.…”
mentioning
confidence: 99%